2018
DOI: 10.11648/j.ijnfs.20180704.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa Leaves Powder Consumption on Young Children Nutritional and Serum Retinol Status in Burkina Faso Rural Area

Abstract: The promotion of the consumption of indigenous plant species with high nutritional value is an important nutrition intervention in Africa rural areas. The current student was a randomized control trial of two groups (ᶲG₥ and ᶲGm) with a baseline and an endline evaluation after 12 weeks. A total of 119 pre-school children received Moringa leaf powder and changes in vitamin A and anthropometric indicators of children were assessed against changes for control group children. After 12 weeks, the mean WHZ reflectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…The results of this study are consistent with studies in Bangalore India, which 60% of children who were given 15 grams of Moringa leaf powder twice a day for two months improving their nutritional status from grade I protein energy malnutrition to normal nutritional status [33]. Other studies in Burkina Faso also shown that malnourished children who were given 10 grams of Moringa leaf powder daily for 6 months improved their anthropometric status [34]. Supplementation of 5-10 grams of moringa oleifera powder per daily for 14 days has been able to increase body weight by 0.53 kilograms on children in Kupang Regency [35].…”
Section: B Discussionsupporting
confidence: 91%
“…The results of this study are consistent with studies in Bangalore India, which 60% of children who were given 15 grams of Moringa leaf powder twice a day for two months improving their nutritional status from grade I protein energy malnutrition to normal nutritional status [33]. Other studies in Burkina Faso also shown that malnourished children who were given 10 grams of Moringa leaf powder daily for 6 months improved their anthropometric status [34]. Supplementation of 5-10 grams of moringa oleifera powder per daily for 14 days has been able to increase body weight by 0.53 kilograms on children in Kupang Regency [35].…”
Section: B Discussionsupporting
confidence: 91%
“…Indigenous nutrient-rich plant sources like Moringa oleifera are increasingly discussed as potential sustainable solution to combat malnutrition in children [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102]. Descriptive studies (intra-group comparisons) comment positively on MLP application as preventive or treatment approach however bear distinct limitations:…”
Section: Nutrition Intervention Studies Including the Feeding Of Morimentioning
confidence: 99%
“…Hereby the admission period for SAM children aged 6 to 59 months accounted for an average of 36 days (IG) and 57 days (CG) due to significant higher weight gains in IG (8.9g/kg/d) versa CG (5.7 g/kg/d), respectively. Another trial by Zongo et al[97] conducted in Burkina Faso on pre-school children aged 12 to 59 months was ineffective in changing the nutritional status (HAZ, WHZ) by applying 30g MLP over the day for 12…”
mentioning
confidence: 99%
“…Moringa products are often promoted as nutritional supplements to treat and prevent micronutrient malnutrition such as vitamin A deficiency, which is prevalent in many parts of Africa or South Asia ( 18 ). As such tropical and subtropical countries are home to the drumstick tree, several studies investigated the potential of Moringa oleifera products as a vitamin A source ( 16 , 17 , 19 , 20 ). Borges Teixeira et al ( 16 ) revealed a mean beta-carotene content of 161 μg/g and a mean lutein content of 47 μg/g lyophilized leaf flour.…”
Section: Introductionmentioning
confidence: 99%